2016
DOI: 10.1080/2162402x.2016.1170264
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular HSP110 skews macrophage polarization in colorectal cancer

Abstract: HSP110 is induced by different stresses and, through its anti-apoptotic and chaperoning properties, helps the cells to survive these adverse situations. In colon cancers, HSP110 is abnormally abundant. We have recently showed that colorectal cancer (CRC) patients with microsatellite instability (MSI) had an improved response to chemotherapy because they harbor an HSP110 inactivating mutation (HSP110DE9). In this work, we have used patients' biopsies and human CRC cells grown in vitro and in vivo (xenografts) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 48 publications
4
44
0
Order By: Relevance
“…Another recent study revealed that the HSP110 expression status is associated with differential polarization of tumor‐associated macrophages in colon cancer. In detail, colon cancer with high expression of HSP110 was associated with infiltration of pro‐tumoral macrophages, whereas colon cancer with low expression of HSP110 was associated with infiltration of anti‐tumoral macrophages . This evidence indicates that HSP110 biologically facilitates the progression of CRCs and supports recent observations that decreased expression of HSP110wt with HSP110 T 17 deletions is associated with an improved prognosis of MSI‐H CRCs.…”
Section: Discussionsupporting
confidence: 84%
“…Another recent study revealed that the HSP110 expression status is associated with differential polarization of tumor‐associated macrophages in colon cancer. In detail, colon cancer with high expression of HSP110 was associated with infiltration of pro‐tumoral macrophages, whereas colon cancer with low expression of HSP110 was associated with infiltration of anti‐tumoral macrophages . This evidence indicates that HSP110 biologically facilitates the progression of CRCs and supports recent observations that decreased expression of HSP110wt with HSP110 T 17 deletions is associated with an improved prognosis of MSI‐H CRCs.…”
Section: Discussionsupporting
confidence: 84%
“…On the contrary, further work demonstrated inhibittory effects of extracellular HSPH1 and HYOU1 upon macrophage differentiation, favoring a pro-tumor phenotype [10]. …”
Section: Damp Vs Damper—dual Role Of Extracellular Hsps?mentioning
confidence: 99%
“…The release of HSP110 from human intestinal epithelial cells has also been described, suggesting a role in the physiological process of epithelial renewal [160]. More recently, we have demonstrated that HSP110, like other HSPs, can be secreted by cancer cells and is abundantly observed in the cancer microenvironment [161]. Interestingly, extracellular HSP110 affects macrophage differentiation/polarization by favoring a protumor, anti-inflammatory profile and the formation of tumor-associated macrophages (TAMs), which are associated with immune suppression.…”
Section: Hsp110 Functionsmentioning
confidence: 63%
“…Interestingly, extracellular HSP110 affects macrophage differentiation/polarization by favoring a protumor, anti-inflammatory profile and the formation of tumor-associated macrophages (TAMs), which are associated with immune suppression. Furthermore, we found a correlation between the level of extracellular HSP110 and the number of TAMs in patient biopsies [161], suggesting that the effect of extracellular HSP110 function on macrophages may also contribute to the poor outcomes that are associated with HSP110 expression. two forms of HSP110, their differential roles remain unclear.…”
Section: Hsp110 Functionsmentioning
confidence: 76%